Out of this WORLD. - Haynes, Natalie (New Humanist)
The article examines the rise in popularity of science-fantasy on television. According to the author, the increasing popularity of science-fantasy on television must be partly because programs set in the real world have become increasingly limited in scope. It is said that the science-fantasy has become the natural home for big political issues and has always acted as a metaphor for writers to comment on the real world.